1997
DOI: 10.1089/thy.1997.7.613
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Changes in Patients with Thyroid Cancer After Withdrawal of Thyroid Hormone Therapy

Abstract: Quality of life (QOL) is an important consideration as patients survive longer with cancer and is an area of increasing interest in patients with thyroid cancer who undergo long-term cancer surveillance. However, there are few disease-specific QOL tools available to evaluate QOL in patients with thyroid cancer. The purposes of this longitudinal, repeated-measures study were to: (1) test a new instrument, the QOL-Thyroid Scale, during thyroid hormone withdrawal; and (2) to evaluate the impact of thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
171
0
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(190 citation statements)
references
References 7 publications
10
171
0
9
Order By: Relevance
“…Most studies on thyroid cancer survivorship in North America have reported a modest decrease in quality of life (QoL) after treatment (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, careful review of these data shows that the study populations were small, the tools were inconsistent and not tailored for thyroid cancer survivors, the sampling techniques did not take into account the varied survivor populations found in modern society, and only five small studies were conducted in the United States (12,14,16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on thyroid cancer survivorship in North America have reported a modest decrease in quality of life (QoL) after treatment (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, careful review of these data shows that the study populations were small, the tools were inconsistent and not tailored for thyroid cancer survivors, the sampling techniques did not take into account the varied survivor populations found in modern society, and only five small studies were conducted in the United States (12,14,16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during withdrawal, patients show associated psychological symptoms and social changes, such as family distress or decreased motivation to work. Patients suffering from non-metastatic DTC have been shown to have worse HRQL during peak thyroid withdrawal (5,6). Several years ago, recombinant human TSH (rhTSH) was introduced and this avoids the side-effects of thyroid hormone withdrawal (4).…”
Section: Introductionmentioning
confidence: 99%
“…L-T4 withdrawal also results in a lengthy period of hypothyroidism of variable, but often marked, severity (1). This metabolic impairment may lead to adverse clinical consequences such as occasional cases of ischaemic heart disease or dementia, and, particularly when bone metastases are present, compressive symptoms due to tumour growth stimulation (2).…”
Section: Introductionmentioning
confidence: 99%